Non-exposure parenting increases risk of bullying behavior in junior high school students - Hasan, Surilena; Jessica, Jessica (Universa Medicina, 2016)
Background Bullying behavior is one of many behavioral and disciplinary problems among school students, which has a wide impact on youth, families, schools, and communities. Parenting and the role of parents as good educators (exposure) can prevent mental, emotional and behavioral disorders caused by bullying. The aim of this study was to determine the role of self-esteem and family factors on bullying behavior in junior high schools students.MethodsA cross-sectional study was conducted including 1324 junior high school students of Penjaringan village, North Jakarta. Respondents filled out questionnaires on demographics (age, gender, economic status, educational level), Rosenberg self-esteem questionnaire, strength and difficulties questionnaire, Olweus bullying questionnaire, Hamilton scale for depression, parenting style, and family adaptability and cohesion scales III. Simple and multivariate logistic regression tests were used to analyze the data.ResultsRespondents consisted of 53.5% females and 46.5% males, with an age range of 13-16 years. A total of 45% was involved in bullying (victims, perpetrators, and victims and perpetrators). Gender, self-esteem, family relationships, and parenting were significantly associated with bullying role (p<0.05). Multiple logistic regression analysis showed that self-esteem (odds ratio=23.89; 95% CI:7.899-12.990) and non-exposure parenting (odds ratio=39.11;95% CI: 2.455-8.210) were significantly associated with bullying behavior. ConclusionsNon-exposure parenting was the most relevant risk factor of bullying behavior. Low self-esteem increases the risk of bullying behavior. These findings suggest the need of timely bullying prevention and intervention programs that should have a special focus on families of primary high school students.